Comparing the phonological, musical, and general cognitive profiles of early-emerging poor, average, and good readers of Chinese - Choi, William; Bautista, Alfredo; Kong, Siu-Hang; Lai, Veronica Ka Wai (Frontiers in Psychology, 2025)
IntroductionThis study compared the phonological, musical, and general cognitive profiles of early-emerging poor, average, and good readers.MethodsWe assessed Cantonese preschool children on Chinese word reading, phonological awareness, lexical tone awareness, musical rhythm perception, musical pitch perception, working memory, and non-verbal intelligence.ResultsEarly-emerging poor readers exhibited poorer phonological awareness than early-emerging average and good readers, whereas the latter two groups did not differ significantly. In the working memory task, early-emerging good readers outperformed both early-emerging average and poor readers, who performed similarly. No significant group differences were found in lexical tone awareness, musical rhythm perception, musical pitch perception, or non-verbal intelligence.DiscussionThe results reflect phonological deficits in early-emerging poor readers. Furthermore, phonological awareness and working memory were useful for identifying early-emerging poor and good readers, respectively. Clinically, these findings imply that early-emerging poor readers may benefit most from initial phonological awareness training, followed by working memory training. Moreover, working memory training may also be beneficial for early-emerging average readers seeking to improve their Chinese word reading.